2022
DOI: 10.3390/molecules27154972
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Analysis and the Antioxidant and Preventive Actions of Opuntia stricta Juice Extract against Hepato-Nephrotoxicity and Testicular Injury Induced by Cadmium Exposure

Abstract: Opuntia stricta is a rich source of phenolic compounds. This species generally has strong antioxidant activities in vitro and in vivo. This study aimed to analyze the antioxidant properties of phenolic compounds isolated from Opuntia stricta, including its radical scavenging activities and preventive action against Cd-induced oxidative stress in rats. To assess the protection of prickly pear juice extract (PPJE) against Cd-induced hepato-nephrotoxicity and testicular damage, male albino rats received PPJE (250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
1
2
0
1
Order By: Relevance
“…Opuntia stricta juice extract increase SOD, GPx & CAT and decrease MDA levels significantly (p < 0.05) in male albino rat his study revealed that prickly pear juice extract protects against the toxic effects of Cd, possibly through its free radical scavenging and antioxidant activities (Zhu and Athmouni, 2022). Also, these results agree with (Bardaa et al, 2020), (El-Beltagy et al, 2020) & (Elgazar et al, 2023).…”
Section: Biological Evaluationsupporting
confidence: 67%
“…Opuntia stricta juice extract increase SOD, GPx & CAT and decrease MDA levels significantly (p < 0.05) in male albino rat his study revealed that prickly pear juice extract protects against the toxic effects of Cd, possibly through its free radical scavenging and antioxidant activities (Zhu and Athmouni, 2022). Also, these results agree with (Bardaa et al, 2020), (El-Beltagy et al, 2020) & (Elgazar et al, 2023).…”
Section: Biological Evaluationsupporting
confidence: 67%
“…Moreover, O. stricta extracts obtained from flowers and whole fruits or peels exhibited many pharmacological activities such as anti-spermatogenic, hypotensive, anti-oxidant, antibacterial, anti-inflammatory, antiviral, analgesic and anticancer [8][9][10][11][12][13][14][15][16]. These beneficial medicinal features are as a result of their chemical contents of antioxidants, pigments, and phenolic acids [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Zhu X et al [ 39 ] analysed the effect of the phenolic extract isolated from Opuntia stricta cladode juice, from Tunisia, in cadmium- (Cd-)-induced hepatic damage. Therefore, Wistar rats were divided into the following groups: rats receiving just normal saline (G1); rats given cladode juice extract (250 mg/kg b.w./day) (G2); rats administered cadmium chloride (CdCl 2 ) (1 mg/kg b.w./day) (G3); and rats fed with CdCl 2 (1 mg/kg b.w./day) together with cladode juice extract (G4) for five weeks.…”
Section: Effects Of Other Opuntia Species On Liver...mentioning
confidence: 99%